Annual Zoledronic Acid for the Treatment of Osteoporosis: A Randomized Controlled Trial - Asif Hussain; Sushil Kumar Saini; Jaydeep Patel; Chandra Prakash Pal; Hemant Singh Chahar; Rohit Yadav (Journal of Orthopedics, Traumatology and Rehabilitation)
Context: Osteoporosis remains a significant public health problem in many parts of the world, including India. The efficacy of oral bisphosphonates is lower because of poor compliance. Annual treatment with zoledronic acid has been reported to improve outcomes. Objective: To study the benefits and side effects of zoledronic acid in patients with osteoporosis. Methods: This is a blinded randomized clinical trial conducted at a government hospital. Patients aged 50–89 years with bone mineral density (BMD) T score < −2.5 or < −1.5 with 2 mild vertebral fractures or 1 moderate vertebral fractures were randomized to receive placebo versus zoledronic acid. A total of 200 patients were be studied, 100 in each arm. Zoledronic acid was given in single dose (15-min infusion). Serum calcium, dual-energy X-ray absorptiometry, and lateral spine radiographs were performed at enrollment and after 12 months. The primary endpoint was combined risk of new-onset vertebral and hip fractures. The secondary endpoints were new-onset vertebral and hip fractures and BMD. Results: The primary outcome was reduced by 79% during the 1-year period in zoledronic acid, compared to placebo (3% in the treatment group vs. 14% in the placebo group; relative risk (RR): 0.21; 95% confidence interval [CI]: 0.06–0.72, P = 0.01). Treatment with zoledronic acid reduced the risk of new-onset vertebral fracture by 82% (RR: 0.18; 95% CI: 0.04 to 0.79; P = 0.02). No significant differences in new-onset hip fractures were noted (RR: 0.33; 95% CI: 0.03–3.15; P = 0.33). A significant increase in BMD score was found after treatment with zoledronic acid compared to placebo group (P < 0.05). No serious adverse events were noted. Conclusion: Annual infusion of zoledronic acid reduces the risk of combined fracture of vertebra and hip and improves the bone mineral density in osteoporotic patients.